Pengaruh Kualitas Produk, Harga, Citra Merek Terhadap Keputusan Pembelian Motor Kawasaki Ninja(Studi Pada Masyarakat di Kota Surakarta) - Yudha, Yulio Angga, Dra. Wuryaningsih Dwi Lestari, M.M (2016)
This study aims to determine the effect of product quality, price, brand image to the purchasing decision Kawasaki Ninja motorcycle. The sample in this study is the people who use the products Kawasaki Ninja motorcycle in Surakarta totaling 100 respondents. The sampling technique in this research is purposive sampling. Data analysis method used is validity, reability, normality test and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). In this study the data meet for a normal distribution. Hypothesis tests showed the product quality, price, and brand image have significant influence with t respectively for 2231, 2089 and 6297. In the F test showed that jointly variable product quality, price, and brand image significantly influence purchasing decisions with a probability value of 0.000 (0.000 <0.05). The coefficient of determination (R2) of 50.4%. Keywords: product quality, price, brand image and purchase decisions.